2020
DOI: 10.1111/cch.12820
|View full text |Cite
|
Sign up to set email alerts
|

Youth with disabilities are more likely than their peers to engage in hazardous child labour

Abstract: Background: Little is known about the extent to which children and adolescents with disabilities are exposed to child labour. Objective: To estimate prevalence rates and adjusted rate ratios of exposure to child labour among children and adolescents with/without disability in middle-and lowincome countries and to determine whether these rates vary between functional limitations associated with disability. Participants and Setting: Nationally representative samples involving 142,499 children aged 5-14 from 15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Our findings show large and prevalent inequities by disability in hazardous working conditions in six countries among girls and seven countries among boys out of 24 countries included, and often in different countries. These findings are consistent with two other studies using different samples of MICS data [ 7 , 11 ], including a study drawing on data from 15 countries, which found that children with disabilities were 4% more likely than children without disabilities to be in child labour and 18% more likely to work under hazardous conditions [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings show large and prevalent inequities by disability in hazardous working conditions in six countries among girls and seven countries among boys out of 24 countries included, and often in different countries. These findings are consistent with two other studies using different samples of MICS data [ 7 , 11 ], including a study drawing on data from 15 countries, which found that children with disabilities were 4% more likely than children without disabilities to be in child labour and 18% more likely to work under hazardous conditions [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, few studies exist on inequities in birth registration by disability status. The limited available evidence shows that children with disabilities are more likely be in child labour [7,10,11], and approximately twice as likely to experience violence compared to children without disabilities, with a higher prevalence of violence in lowand middle-income countries (LMICs) [12]. A higher prevalence of child labour and violence among children with disabilities is unfair, unjust, and preventable, and constitutes a health inequity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The current study adds to the evidence base by demonstrating that children working under hazardous work conditions with/without child labour have greater psychosocial functioning difficulty. This is consistent with a secondary analysis of the UNICEF MICS data from 15 countries which showed that children with disability, particularly those who had poor mental health or cognitive functioning, were more likely to be exposed to hazardous child labour [ 22 ]. Furthermore, a multi-national study from Afghanistan, Bangladesh, Nepal and Pakistan helps to decipher some of the psychosocial features affected by work among youth in the brick industry.…”
Section: Discussionsupporting
confidence: 89%